Do migrant remittances decline income gap in the MENA region? - Elorabi, Khaled; Ishak, Suryati; Mohamed Nor, Norashidah; Ibrahim, Saifuzzaman (Human Resource Management Academic Research Society, 2023)
This paper investigates the impact of inward remittances on income inequality in thirteen Middle East and North Africa (MENA) economies, spanning from 1996 to 2020, employing the pooled mean group (PMG) technique. This article reveals that remittances from migrants to the MENA region contribute to increased income inequality, indicating that the households receiving these remittances are initially relatively well-off, and the funds significantly enhance their living standards in comparison to other families. Consequently, the paper suggests addressing challenges faced by low-income individuals aspiring to migrate, particularly in nations with high unemployment rates. These challenges encompass educational and skill deficits, information disparities, and financial limitations. Furthermore, the paper proposes implementing supplementary policies to counteract the adverse effects of remittances on income distribution, including directing resources towards initiatives that benefit the less affluent, particularly those focused on improving education, healthcare, and infrastructure. Lastly, it emphasizes the importance of prioritizing policies that foster political stability to create a business environment conducive to human and infrastructure investments.